Understanding the performance of HIV-1 viral vector vaccines: adenovirus and poxvirus case studies - Manafi, Mahdiyeh M.; Farzani, Touraj; Espinoza, Nallely; Ozonoff, Al; Sabeti, Pardis C. (Frontiers in Immunology, 2026)
Despite decades of research, HIV-1 continues to infect millions annually, underscoring the urgent need for a safe and effective vaccine to curb the ongoing global pandemic. Among the many strategies explored, viral vectors have been the most intensively studied, with adenoviral and poxviral platforms serving as the leading approaches. These vectors have advanced through extensive preclinical evaluation and multiple large-scale clinical trials, demonstrating safety and the ability to induce cellular and humoral responses. Yet, they have also revealed key challenges, including pre-existing vector immunity, limited durability of responses, and in some cases, increased susceptibility to infection. Importantly, these trials clarified the limitations of Env-focused immunity, highlighted the value of heterologous prime–boost regimens, and reinforced the dual need for broadly neutralizing antibodies and functional T cell responses. While vector-based COVID vaccines achieved protective efficacy, lessons learned from adenoviral and poxviral efforts continue to shape the field, directly informing the design of next-generation platforms such as mRNA and engineered viral vectors.